Paulo Freire e a educa????o infantil: a experi??ncia de Chapec?? - Scherer, Ana Paula de Oliveira (2011)
The present text had as its objective to study the Political Pedagogical Project (PPP) developed in kindergarten of Chapec?? (SC, Brasil) in the period of (1999-2004). The research investigated both the freirian categories and the principles of the municipal curricular proposition, confronting them. It also studied the process of interpretation, assimilation, adhesion and application, by the teachers of childhood education of Chapec??, of the proposed project. This study justifies itself, among other reasons, in the verification of pertinence of application of freirian theory in this grade, as Paulo Freire created his methodology to apply it in adult education, despite its reception in so many areas of knowledge and education.